Secondary infections in COVID-19: Antemortem and postmortem culture study - Vandana V. Kiro; Meenakshi Sharma; Sharad Srivastava; Parin Lalwani; Richa Aggarwal; Kapil D. Soni; Rajesh Malhotra; Sanjeev Lalwani; Purva Mathur; Anjan Trikha (Indian Journal of Pathology and Microbiology)
Background: Secondary bacterial infections during COVID-19 hospitalization have been reported in about 6–15% of patients. Aims: To study the secondary bacterial infections that affected the COVID-19 patients during their hospitalisation and to unearth the bacteriological profile of samples obtained after their demise. Settings and Design: This prospective study was carried out at a COVID-19 dedicated, apex tertiary care centre in North India from July 2020 to April 2021. Methods and Materials: Samples of 268 patients were considered for the study. Nasopharyngeal swab specimen, blood, and tissue (lung) were collected from the deceased body as early as possible and processed. Statistical Analysis: Statistical analyses were performed using STATA version 11.1 (Stata Corp., College Station, TX, USA). Results: A total of 170 samples were received from patients before their death, which included blood, urine, respiratory samples, pus, and cerebrospinal fluid. Forty-four pathogens were isolated, which consisted of Acinetobacter baumannii (43.1%), Klebsiella pneumoniae (36.3%), Escherichia coli (11.3%), and Pseudomonas aeruginosa (4.5%), Enterococcus faecium (4.5%). Two hundred fifty-eight samples were collected from the deceased bodies wherein the nasopharyngeal sample was highest, followed by tissue and blood. A total of 43 pathogens were isolated among them which included A. baumannii (44.1%), followed by K. pneumoniae (25.5%), E. coli (20.9%), P. aeruginosa (6.97%) and Enterobacter cloacae (2.3%). All these isolates were highly resistant to antimicrobials. Conclusions: In our study, bacterial profiles in antemortem and postmortem samples were found to be similar, suggesting that resistant pathogens may be the cause of mortality in COVID-19 infected hospitalised patients.